2018
DOI: 10.1111/aos.13722
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of intraocular pressure after bariatric surgery

Abstract: In a cohort of obese individuals undergoing sleeve gastrectomy, there was a significant decrease in IOP measured 3-6 months after the procedure. Our results suggest that significant weight loss could have beneficial effects on IOP in obese individuals with ocular hypertension which might enable avoidance of antiglaucoma medications. The high likelihood of a reduction in IOP should be taken into account when considering bariatric surgery in such patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…Studies done by Viljanen et al 9 as well as Burgansky-Eliash et al 4 on the effect of bariatric surgery on the IOP showed similar results, however, they were at 6 months postoperatively.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Studies done by Viljanen et al 9 as well as Burgansky-Eliash et al 4 on the effect of bariatric surgery on the IOP showed similar results, however, they were at 6 months postoperatively.…”
Section: Discussionmentioning
confidence: 65%
“…The excessive intraorbital adipose tissue, increased episcleral venous pressure, and impairment in aqueous outflow facility may have exerted mechanical effect on the IOP in obese patients that got relieved after significant weight reduction. 8 Studies done by Viljanen et al 9 as well as Burgansky-Eliash et al 4 on the effect of bariatric surgery on the IOP showed similar results, however, they were at 6 months postoperatively.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Burgansky-Eliash [19] and Çekic [20] suggested the possibility that reduction of blood pressure after sleeve gastrectomy in obese patients may be associated with a reduction of IOP and a better retrobulbar blood flow. Increased risk for primary open-angle glaucoma (POAG) in obese subjects has been reported [21] and beside the increase of IOP, several others may be the mechanisms of damage involved: trabecular meshwork malfunctioning [22], increased oxidative stress [23], decreased aqueous outflow caused by increased orbital fat [24] and impairment of retrobulbar blood flow [20].…”
Section: Discussionmentioning
confidence: 99%